Identification of indicators for the implementation of a traceability system for shark and ray products among intermediaries in Pahang, Malaysia - YUSOF, ROBA’A; SHUIB, AHMAD; RAMACHANDRAN, SRIDAR (Universiti Malaysia Terengganu, 2024)
Traceability system implementation has been suggested to improve data collection in shark and ray product supply chains, thereby supporting their sustainable utilisation and trade. By providing sufficient supply chain information, this system can help to prevent illegal, unreported and unregulated (IUU) fishing and the extinction of these important species. This study aimed to identify the indicators for implementing a traceability system for shark and ray products among intermediaries in Pahang. The study employed a descriptive analysis utilising a reliability test, Exploratory Factor Analysis, and frequency analysis. Individual interviews were conducted using semi-structured questionnaires. The study identified 21 indicators categorised from four dimensions: Shark and ray resources, regulatory compliance and collaboration effort, commitment and skills, and information technology infrastructure. The government is recommended to enforce mandatory registration of intermediaries, require species-specific reporting, invest in management and financial support, increase awareness and training, improve current information system infrastructure, and maintain good collaboration with all stakeholders. Future studies should include consumers and the community to raise awareness about shark and ray products and promote their sustainable utilisation and trade.